2015
DOI: 10.1259/bjr.20140852
|View full text |Cite
|
Sign up to set email alerts
|

Radiation doses from fluoroscopically guided cardiac catheterization procedures in children and young adults in the United Kingdom: a multicentre study

Abstract: This is the first large-scale, patient-specific assessment of organ doses from these procedures in a young population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 36 publications
1
47
1
Order By: Relevance
“…Installation of next generation catheterization laboratory equipment may further result in substantial radiation dose reduction without necessitating changes in exposure settings or resulting in loss of image quality . Efforts to minimize radiation exposure as low as reasonably achievable (the ALARA principle) while maintaining “optimization” of imaging protocols have driven advances and refinement of operator techniques to ensure ongoing decreases in radiation exposure . The impact of these ongoing improvements on radiation dose reduction, as demonstrated in this study, suggests that benchmarks should be periodically revised to reflect broad reductions in radiation doses .…”
Section: Discussionmentioning
confidence: 87%
“…Installation of next generation catheterization laboratory equipment may further result in substantial radiation dose reduction without necessitating changes in exposure settings or resulting in loss of image quality . Efforts to minimize radiation exposure as low as reasonably achievable (the ALARA principle) while maintaining “optimization” of imaging protocols have driven advances and refinement of operator techniques to ensure ongoing decreases in radiation exposure . The impact of these ongoing improvements on radiation dose reduction, as demonstrated in this study, suggests that benchmarks should be periodically revised to reflect broad reductions in radiation doses .…”
Section: Discussionmentioning
confidence: 87%
“…Considerable variation in dose is seen, however, from one procedure to the next, or between different centres, depending on equipment and technique preferences. 2 Risk estimates based on 25th percentiles of organ doses (shown in the online supplementary materials) were around 40% lower than those based on median doses, while those based on 75th percentiles are around 80% higher. The presented risk estimates are based on median ages at which each procedure is done.…”
Section: Discussionmentioning
confidence: 93%
“…The methodology for dose estimation has been described previously. 2 Briefly, examination-specific organ doses were estimated from dose indicators recorded at the time of each examination (kerma area product (P KA ), also known as dose area product), using a dosimetry system based on Monte Carlo simulations (PCXMC V2.0), and incorporating data on projection angles and beam energy obtained from a sample of structured dose reports recorded for clinical examinations. A number of modifications have since been made, including increasing the field size for some procedure types, varying X-ray energy according to patient size and accounting for table attenuation.…”
Section: Methodsmentioning
confidence: 99%
“…The number of paediatric cardiac catheterisation procedures has continued to increase over the last decade [1] due to their value in diagnosing and in particular, treating congenital heart disease. Unfortunately paediatric cardiac catheterisation contribute a significant radiation burden to children who are 2 -10 times more sensitive to radiation-induced cancer compared to adults [2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately paediatric cardiac catheterisation contribute a significant radiation burden to children who are 2 -10 times more sensitive to radiation-induced cancer compared to adults [2][3] . The largest dosimetry study for paediatric cardiac catheterisation in the United Kingdom, consisted of >10,000 procedures and demonstrated that almost 50% of children had received radiation doses comparable to having >500 chest radiographs [4] . The lifetime risk of developing any cancer for children in receipt of numerous medical imaging examinations for congenital heart disease has been reported to be as high as 6.5% [5] .…”
Section: Introductionmentioning
confidence: 99%